Conducting Tests on the Competencies of A Future Teacher Teaching A Foreign Language - Kadyrova Madinabonu; Samalikova Ainur Mahataevna (Genius Journals, 2023)
The article examines the system of international assessment of Arabic language proficiency, important personal and social characteristics of the pedagogical competence of a future Arabic teacher in achieving professional success, strategies that a future teacher should follow when teaching Arabic to people who do not speak аrabic.
Keywords: Strategy; pedagogical skills; modern linguistics